2021
DOI: 10.3389/fnhum.2021.660470
|View full text |Cite
|
Sign up to set email alerts
|

Idiosyncratic Characteristics of Postural Sway in Normal and Perturbed Standing

Abstract: ObjectiveAre people with a characteristically large physiological sway rendered particularly unstable when standing on a moving surface? Is postural sway in standing individuals idiosyncratic? In this study, we examine postural sway in individuals standing normally, and when subtle continuous sinusoidal disturbances are applied to their support platform. We calculate consistency between conditions to verify if sway can be considered characteristic of each individual. We also correlate two different aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The data have been collected here and analysed on the basis of one single trial per subject per condition (i.e., the first trial of a series of eight trials), administered in order to investigate the effect of the sensory conditions in the adaptation to repeated stance performances. Given the inter-individual variability in the stance performance (9,176), particularly when standing on foam, this procedure is certainly a limitation however hardly avoidable because repetition of stance trials produces significant adaptation in the balancing pattern (8,127,(177)(178)(179)(180). Alsubaie et al (181) have recently shown that different measures of postural sway are reliable when recorded at two visits 1 week apart, including measures with unstable BoS and sensory conditions.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data have been collected here and analysed on the basis of one single trial per subject per condition (i.e., the first trial of a series of eight trials), administered in order to investigate the effect of the sensory conditions in the adaptation to repeated stance performances. Given the inter-individual variability in the stance performance (9,176), particularly when standing on foam, this procedure is certainly a limitation however hardly avoidable because repetition of stance trials produces significant adaptation in the balancing pattern (8,127,(177)(178)(179)(180). Alsubaie et al (181) have recently shown that different measures of postural sway are reliable when recorded at two visits 1 week apart, including measures with unstable BoS and sensory conditions.…”
Section: Limitationsmentioning
confidence: 99%
“…Body sway when standing upright on a solid base of support is normally almost negligible in healthy subjects, witnessing accurate and precise neural control ( 6 , 7 ) based on the internal model of gravitational and inertial forces ( 8 ) and on multiple inputs from the receptors detecting the body state. The excursions of the centre of foot pressure (CoP) of subjects standing quietly on the firm ground are approximately contained within the size of a dime, even if there is a large variability in sway across different healthy subjects ( 9 ). In several conditions, though, sway area can significantly increase, such as standing on sloped surfaces or when leaning forward or backward ( 4 , 10 ), or decrease when subjects stand on elevated platforms ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this information, maximal angular velocity ( ω max ) in the 3.0–5.0°/s range was assumed in this study, to investigate the effect of the general sway intensity (assuming young and healthy adults) on the human microclimate. As the fluctuation of COP, COM and COP minus COM in measured data corresponds to the postural sway frequency, we set 1.0 Hz for the AP direction and 0.5 Hz for the ML direction, based on the previously reported values 52–55 . The angular velocity and sway frequency of the human body were simplified assuming a sine function, as shown in Figure 13A.…”
Section: Reproduction Of Human Physiological Functions Using the Cspmentioning
confidence: 99%
“…As the fluctuation of COP, COM and COP minus COM in measured data corresponds to the postural sway frequency, we set 1.0 Hz for the AP direction and 0.5 Hz for the ML direction, based on the previously reported values. [52][53][54][55] The angular velocity and sway frequency of the human body were simplified assuming a sine function, as shown in Figure 13A. As a result, the head displacements indicated in Figure 12 for ω max = 3.0, 4.0, and 5.0 °/s were approximately 14.5, 19.3, and 24.1 mm, as summarized in Figure 13B; these values are typical for young and healthy adults.…”
Section: Human Micromotion In the Standing Posturementioning
confidence: 99%
“…The body during quiet stance is inclined slightly forward so that the mean vertical projection of the center of mass (CoM) is on average a few centimeters forward of the ankle joint [1]. This causes a tendency of the body to forward fall, due to gravitational toppling torque.…”
Section: Introductionmentioning
confidence: 99%